HUBUNGAN STATUS GIZI DENGAN PRESTASI BELAJAR SISWA SEKOLAH DASAR DI KECAMATAN MODOINDING - Maleke, Vini; Umboh, Adrian; Pateda, Vivekenanda (e-CliniC, 2015)
Abstract: Nutrition is needed for growth and development, energy, thinking, and physical well-being. Selection of proper nutrition will optimize growth and brain development. This study aimed to determine the relationship of nutritional status and academic achievement of elementary school students in Modoinding. This was a descriptive analytical study with a cross sectional design. The nutritional status was based on BMI value meanwhile the academic achievement was based on school reports. Samples were 114 students. Data were analyzed by using univariate and bivariate analyses as well as ANOVA F test. The results showed that there was no significant relationship between nutritional status and academic achievement with a p value = 0.792. Conclusion: There was no significant relationship between nutritional status and academic achievement among the elementary students in Modoinding. Keywords: nutritional status, achievement Abstrak: Gizi dibutuhkan anak sekolah untuk pertumbuhan dan perkembangan, energi, berpikir, serta daya tahan tubuh. Gizi yang berkualitas akan mengoptimalisasikan pertumbuhan dan perkembangan otak. Penelitian ini bertujuan untuk mengetahui hubungan status gizi dan prestasi belajar siswa Sekolah Dasar Kecamatan Modoinding. Penelitian ini bersifat dekriptif analitik dengan desain potong litang. Status gizi dan prestasi dilihat berdasarkan nilai IMT dan hasil rapor. Jumlah sampel sebanyak 114 siswa. Data dianalisis secara univariat dan bivariat dengan uji anova F. Hasil analisis data memperlihatkan tidak terdapat hubungan bermakna antara status gizi dan prestasi belajar siswa dengan nilai p = 0,792. Simpulan: Pada siswa Sekolah Dasar Kecamatan Modoinding tidak terdapat hubungan bermakna antara status gizi dan prestasi belajar. Kata kunci: status gizi, prestasi